Willingness to pay for future national health insurance scheme: a study among health sector employees in Kuala Lumpur, Malaysia - Hairusnizan Hamzah; Pangie Bakit; Mohamad Azim Noor Azmi; Azimatun Noor Aizuddin; Faiz Daud (Universiti Kebangsaan Malaysia, 2025)
The National Health Insurance (NHI), which utilizes the concept of social health insurance, is a long-term strategy for addressing healthcare costs and rising household out-of-pocket expenditures. This study aimed to determine the willingness to pay (WTP) for NHI among health sector employees and the factors that affect their WTP. A cross-sectional study was conducted among 122 health sector employees of three government health institutions in Kuala Lumpur. A self-administered questionnaire (Cronbach’s alpha 0.78) using the Contingent Valuation Method technique was used to estimate the value of WTP. The response rate was 91.8%. Most respondents (n = 96, 85.7%) were willing to pay for NHI. The mean and median of NHI monthly premiums were RM72.00 (SD RM77.92) and RM50.00 (IQR RM70.00) or 1.94% (SD1.92%) and 1.00% (IQR 1.88%) of respondents’ monthly income. Age (χ2=12.088, p=0.001), household size (χ2 = 5.737, p= 0.017) and total monthly income of respondents (χ2=4.978, p= 0.026) were significant in influencing their WTP for NHI. In conclusion the future NHI scheme will be supported by the majority of health sector employees if the government implements it in Malaysia, based on a sample of 122 employees. Most were willing to pay RM72.00 or 1.94% per month of their total monthly income for NHI. Age, household size, and monthly income were the key factors to consider in planning a successful and sustainable NHI.